PENGARUH PEMBERIAN EDUKASI TENTANG SADARI TERHADAP PELAKSANAAN SADARI PADA REMAJA PUTRI - Chiot, Okti Satria; Andriani, Yessi; Oviana, Athica (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2023)
Based on data (WHO, 2016), says that the number of women, especially young women who suffer from breast cancer reaches 1,150,000, of which 700,000 live in developing countries, one of which is Indonesia. In 2019, the incidence of breast cancer in West Sumatra Province increased to 479 people. This study aims to determine the effect of providing education on BSE on the implementation of BSE in Young Women at SMAN 2 Tilatang Kamang. The research design used the Quasi Experiment method with the research design